Combination therapy with biologic agents in rheumatic diseases: current and future prospects. (October 2016) - Inui, Kentaro; Koike, Tatsuya
Strategies in rheumatoid arthritis (RA) based on 'treat to target' aim to control disease activity, minimize structural damage, and promote longer life. Several disease-modifying antirheumatic drugs (DMARDs) have been shown to be effective including biological DMARDs (bDMARDs). Treatment guidelines and recommendations for RA have also been published. According to those guidelines, conventional synthetic DMARDs (csDMARDs), as monotherapy or combination therapy, should be used in DMARD-naïve patients, irrespective of the addition of glucocorticoids (GCs). Combination therapies with bDMARDs are also essential for conducting treatment strategies for RA, because in every recommendation or guideline for the management of RA, combination therapies of csDMARDs with bDMARDs are recommended for RA patients with moderate or high disease activity after failure of csDMARD treatment. bDMARDs are more efficacious if used concomitantly with methotrexate (MTX) than with MTX monotherapy or bDMARD monotherapy. Thus, retention has been reported to be longer when combined with MTX. The superior efficacy of combination therapy compared with MTX monotherapy or bDMARD monotherapy could be because: (1) it could help to minimize MTX toxicity by reducing the dose of MTX, thus retention rate of the same therapeutic regimen would become high; (2) anti-bDMARD antibodies are observed at lower concentrations when using MTX concomitantly, so less clearance of bDMARDs via less formation of bDMARD and an anti-bDMARD immune complex; (3) of the additive effects of MTX to bDMARD, especially the combination of tumor necrosis factor inhibitors (TNFis) with MTX. Hence, evidence suggests that combination therapy with bDMARDs is more efficacious than monotherapy using a csDMARD or bDMARD, and that MTX is the best drug for this purpose (if MTX is not contraindicated). Finding the most effective drug regimen at the lowest cost will be the aim of RA treatment in the future.